Dynamic responses of a novel floating tapered trash blocking net system due to wave-current combination. (15th December 2022) - Sun, Zhenxiang; Song, Yue; Xie, Mingxiao; Hou, Zhiqiang; Wang, Heng
Abstract: To ensure the safe operation of coastal power plants in nearshore regions, an innovative tapered net system has been widely applied to block the floating bio-fouling and debris. Exposed to the combination of coastal waves and currents, these flexible nets are prone to significant deformation and excessive drawing force, which arises high risk of the system failure. To explore the hydrodynamic performance of the tapered fouling interception system, large-scale model tests have been conducted in wave-current flume under various pure current and wave-current combined conditions. Specifically, a dual-scale similarity is applied in the tapered net model to overcome the dilemma of Reynolds Similarity in Froude scaling tests. The results show that the existence of wave action leads to significant dynamic loading on the connector between the supporting frame and tapered nets, subsequently provoking frequent slack-taut on the connector. This nonlinear characteristics of the drawing force is easier to be triggered by the increased wave height and the enlarged current velocity. Whereas for the effect of wave period, the changing law deviates from the previous studies for a net panel, which demonstrates the importance of the overall shape consideration in the hydrodynamic study of the novel tapered trash blocking system. Highlights: An experimental investigation on the dynamic responses of a novel floating tapered trash blocking net system is conducted due to wave-current combination. Strong nonlinearity of the connecter between is identified with frequent slack-strain force and multiple-frequency characteristics. The influences of wave height, wave period and current velocity on the drawing force of tapered net system are discussed.